Pemberdayaan Penyandang Disabilitas Dalam Meningkatkan Kesiapsiagaan Bencana: Systematic Review - Istiada, Ayu; Ainun Nisa, Alfiana (JUKEJ : Jurnal Kesehatan Jompa, 2025)
This study aims to identify the types of empowerment for persons with disabilities that can enhance disaster preparedness, given that this group faces higher vulnerability to disaster risks. The research employed a systematic review design based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant scientific articles were collected from Scopus, ScienceDirect, and PubMed using English-language keywords. From a total of 1,503 articles identified, 15 were selected through a screening process based on inclusion and exclusion criteria. The findings indicate that social empowerment, community-based empowerment, participatory empowerment, capacity building, and systems and policy-based empowerment significantly improve disaster preparedness knowledge, attitudes, and practices among persons with disabilities. Effective empowerment strategies include preparedness training, involvement in decision-making processes, and the strengthening of social support and access to inclusive information. However, challenges such as limited resources, social stigma, and lack of cross-sectoral coordination remain significant obstacles. In conclusion, empowering persons with disabilities plays a crucial role in enhancing disaster preparedness, highlighting the need for inclusive, participatory, and sustainable strategies to ensure equitable and effective disaster management for all vulnerable groups.